Screening of Antioxidant Activity of Selected Traditionally Used Libyan Medicinal Plant Extracts - Seal C; Wood C, Elmestiri F, (Scientific Journal of University of Benghazi, 2026)
In different parts of the world, the use of medicinal plants has always been important in the therapeutic armory of mankind and remains an important source for the discovery of new bio-active compounds. Libya constitutes an apt example where medicinal plants are widely used. While some individual plant species such as Ginkgo biloba have been investigated in some detail, there is relatively little information available concerning the antioxidant potential of plant species in general and Libyan plants in particular. In this study twenty three Libyan medicinal plants were chosen for the study of antioxidant capacity and phenolic content. Aqueous plant extracts were screened for their antioxidant activity using the FRAP, TEAC and DPPH methods. These methods enable high-throughput screening of potential antioxidant capacity. Results show that of these twenty three plants, hot and cold extracts of Myrtus communis, Quercus robur and Syzygium aromaticum exhibited the strongest antioxidant activity in all tests and this is higher than that of the green tea control. It is suggested that the efficacy of these plants could be explained, at least in part, by their antioxidant activity.